2018
DOI: 10.4269/ajtmh.17-0818
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Chagas Disease in the United States: Cost Savings through Maternal Screening

Abstract: Abstract.Chagas disease, caused by Trypanosoma cruzi, is transmitted by insect vectors through transfusions, transplants, insect feces in food, and from mother to child during gestation. Congenital infection could perpetuate Chagas disease indefinitely, even in countries without vector transmission. An estimated 30% of infected persons will develop lifelong, potentially fatal, cardiac or digestive complications. Treatment of infants with benznidazole is highly efficacious in eliminating infection. This work ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 46 publications
0
38
0
Order By: Relevance
“…Indeed, a recent health economic study in the US evidenced the large benefits of maternal screening for T . cruzi infection, as lifetime societal savings due to screening and treatment was estimated at $634 million saved for every birth year cohort [64].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a recent health economic study in the US evidenced the large benefits of maternal screening for T . cruzi infection, as lifetime societal savings due to screening and treatment was estimated at $634 million saved for every birth year cohort [64].…”
Section: Discussionmentioning
confidence: 99%
“…Ten (0.25%) women had confirmed T. cruzi infection; no infected infants were detected. A recent analysis concluded that in the United States, universal congenital Chagas disease screening and treatment would be cost-saving with congenital transmission rates > 0.001% and maternal prevalence >0.06% (339). The results vary substantially depending on the cost and performance of the maternal screening test; thus, it will be essential to ascertain the currently unknown sensitivity of available serological assays in at-risk populations in the United States.…”
Section: Public Health Approachesmentioning
confidence: 99%
“…Healthcare personnel are often unfamiliar with the risk of congenital transmission [52]. Screening of pregnant women is far from universal, and totally absent in some affected countries [53,54,55], despite the demonstrated cost-effectiveness of these programmes in both endemic and non-endemic settings [53,55,56]. The regional initiative Eliminating Mother to Child Transmission Plus, launched by PAHO in 2017 [57], works to strengthen health systems in participating countries to interrupt congenital transmission of CD along with other congenitally transmitted infectious diseases, although the recommendations in this document are far from being widely adopted in the region.…”
Section: Preventing Congenital Transmissionmentioning
confidence: 99%